Limites à aplicação da teoria dos motivos determinantes do ato administrativo - Maria Leticia Rodrigues Guimaraes Araujo (2016)
The objective of this dissertation is to review the self-determination theory of an administrative act, that originated from the French State Council jurisprudence and was doctrinally developed by Gaston Jeze, as he proposed to review its understanding and its effects. As we apply the theory, we can claim that the motives given in the motivation of the administrative act links the administrator, in a way that if they are invalidated or inexistent, it necessarily entails, the invalidation of the act. The motive is what boosts and justifies the actions of the administrator, thus this being the reason for the theory to appear correct. However, we need to reflect about the existence of limits to its application. This research shows that what is evaluated is the application of homeland doctrine, so as to generalize the liabilities of the theory, needing to be reviewed. Situations in which the above reason in the motivation of the administrative act is inexistent or unsuitable to its respective content, but for the verification of another phatic occurrence, duly qualified by law to be apt to justify the same result, deserves to be considered as a hypothesis for removal of said theory. It is the cause for an accidental error, that distorts the volitional manifestation of the public agent, but that does not change the deponents will. The theme problem becomes even more thought provoking as we face the distinctive premises adopted by Gaston Jeze and by most of the homeland doctrine, when it comes to, above all, the concept of the motive subjective or objective. The evaluation of the formulation context of the theory and the considerations of the principals of juridically, the stability of relations already constituted and the best treatment of public interest, as well as the evolution of the understanding of discretion and link, reinforce the proposal of limits to the application of the self-determination theory. Therefore, the validation stands out as an important instrument of restoration of legality, with regard to the flaw of the motive and/or motivation. From that, we verify the adjustment of the removal of the self-determination theory, in situations where we can check the real motives rising the same content of the act, by the duty of validation of the existing flaw, being it in the motive and/or motivation.